Intervening on conflict, parental bonds, and sexual risk acts among adolescent children of mothers living with HIV. - Mary Jane Rotheram-Borus; Judith A Stein; Eric Rice (PLoS ONE, 2014)
In 1993-1994, a psychosocial intervention conducted in New York City significantly improved outcomes for parents living with HIV and their adolescent children over six years. We examine if the intervention benefits are similar for adolescents of mothers living with HIV (MLH) in 2004-2005 in Los Angeles when MLH's survival had increased substantially.Adolescents of MLH in Los Angeles (N = 256) aged 12-20 years old were randomized with their MLH to either: 1) a standard care condition (n = 120 adolescent-MLH dyads); or 2) an intervention condition consisting of small group activities to build coping skills (n = 136 adolescent-MLH dyads, 78% attended the intervention). At 18 months, 94.7% of adolescents were reassessed. Longitudinal structural equation modeling examined if intervention participation impacted adolescents' relationships with parents and their sexual risk behaviors.Compared to the standard care, adolescents in the intervention condition reported significantly more positive family bonds 18 months later. Greater participation by MLH predicted fewer family conflicts, and was indirectly associated with less adolescent sexual risk behavior at the 18 month follow-up assessment. Anticipated developmental patterns were observed--sexual risk acts increased with age. Reports were also consistent with anticipated gender roles; girls reported better bonds with their mothers at 18 months, compared to boys.Adolescents of MLH have better bonds with their mothers as a function of participating in a coping skills intervention and reduced sexual risk-taking as a function of MLH intervention involvement.